2015
DOI: 10.1364/oe.23.0a1111
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared tailored thermal emission from wafer-scale continuous-film resonators

Abstract: We experimentally investigate the near-infrared emission from simple-to-fabricate, continuous-film Fabry-Perot-type resonators, consisting only of unstructured dielectric and metallic films. We show that the proposed configuration is suitable for realization of narrowband emitters, tunable in ranges from mid- to near-infrared, and demonstrate emission centered at the wavelength of 1.7 μm, which corresponds to the band gap energy of GaSb-based photodetectors. The emission is measured at 748 K and follows well t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In general, the resonant effect is an effective method to enhance the absorption or emission of materials. [14][15][16][17] In the mid-and far-infrared, graphene provides strong plasmonic resonances, which have been widely exploited to enhance the absorption of graphene. [18][19][20] In the visible and nearinfrared, the absorption of graphene was normally enhanced by coupling graphene with dielectric [21][22][23][24][25] or metallic resonant structures.…”
Section: Doi: 101002/adom201600481mentioning
confidence: 99%
“…In general, the resonant effect is an effective method to enhance the absorption or emission of materials. [14][15][16][17] In the mid-and far-infrared, graphene provides strong plasmonic resonances, which have been widely exploited to enhance the absorption of graphene. [18][19][20] In the visible and nearinfrared, the absorption of graphene was normally enhanced by coupling graphene with dielectric [21][22][23][24][25] or metallic resonant structures.…”
Section: Doi: 101002/adom201600481mentioning
confidence: 99%
“…We have previously demonstrated that a simple continuous-layer Fabry-Pérot resonator (cl-FPR), with a dielectric layer sandwiched between two gold mirrors, can act as a thermal emitter with a tunable emission maximum placed at 1.7 µm, corresponding to the bandgap energy of GaSb [42]. However, such selective emitters degrade above 748 K due to the use of gold, which is a poor high-temperature material because of a low melting point and high diffusivity in many dielectrics.…”
Section: Introductionmentioning
confidence: 99%
“…However, such selective emitters degrade above 748 K due to the use of gold, which is a poor high-temperature material because of a low melting point and high diffusivity in many dielectrics. [42]. These shortcomings of gold can be overcome by TiN [43], which has a bulk melting point of 3200 K and chemical inertness up to 1175 K in dry, ambient atmosphere [44].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible solution to achieving spectral selectivity, which will be discussed in the next section, is to place thin film emitters on top of optimally designed substrates or embed them into planar Fabry-Perot optical cavities. Selective absorbers and emitters designed using this approach have been successfully demonstrated both theoretically and experimentally [107,[156][157][158][159].…”
Section: Selective Surfaces For Solar Thermal Energy Generationmentioning
confidence: 99%